Написи на саркофазі з Кирилівської церкви Києва - Марголіна, І.; Бабич, Є. (Сiверянський літопис, 2022)
Мета статті: дослідити нові відомості про давні поховання на теренах Кирилівської обителі Києва. Завдання дослідження: доповнити знання про Кирилівський некрополь і спробувати визначити належність саркофага, описаного в архівному документі, представникам родини засновника храму, а також стимулювати нові археологічні дослідження під підлогою Кирилівської церкви. Актуальним залишається вивчення й оприлюднення національної спадщини, якою є збережена з
ХІІ ст. архітектурно-історична пам’ятка – Кирилівська церква. Осмислення нових отриманих відомостей про древні поховання на теренах Кирилівського храму, про які йдеться в статті, має
безперечну наукову новизну. Висновки. Дослідження архівного документа відкрили можливість зазирнути в давню історію Кирилівської обителі, зробити припущення щодо належності саркофага,
віднайденого під підлогою храму, польській князівні Марії Казимирівні. Принагідно згадано непересічну постать із історії музею «Кирилівська церква», вченого-археолога і музеєзнавця І.І. Мовчана. The purpose of the publication is to study new data on old burials on the territory of St. Cyril
dwelling in Kyiv. Tasks of the research is to supplement the knowledge about the necropolis of St. Cyril
Church and try to determine the affiliation of the sarcophagus described in the archival document to the family
of the founder of the church, as well as to stimulate new archaeological research under the floor of
St. Cyril Church. The study and publication of the national heritage that is an architectural and historical
monument Cyrilʼs Church, which has been preserved since the XIIth c., remains relevant. The comprehension
of the new data obtained on the old burials in the territory of Cyril’s temple, which are discussed in
the article, has an indisputable scientific novelty. Conclusions. The study of the archival document opened
an opportunity to look into the old history of St. Cyril’s monastery, to make assumptions about the belonging
of the sarcophagus found under the floor of the church to the Polish princess Maria Kazymyrivna. An
extraordinary figure in the history of the museum «Cyrilʼs Church», archaeologist and museumist
I.I. Movchan was mentioned.